Pemanfaatan Breksi Batu Apung Asal Pleret Untuk pembuatan Bata Ringan Sebagai Pengganti Bata Merah Pejal - Perpustakaan UGM, i-lib ([Yogyakarta] : Unit Informasi Inovasi Proses Pembelajaran (UI2P2) Universitas Gadjah Mada, 2003)
In recent years low cost housing was developed by the government to accommodate the increasing of Indonesian population. The consequence is the necessaries of building materials, such as normal concrete blocks or fire bricks, are increased. As the fire bricks are made from fire-clay that was taken from rice field regions, the regions could become a bare regions, as seen in Pleret, Bantul, Yogyakarta. An attempt to reduce the damage of rice field regions need to be taken by changing the use of the fire bricks with other material, such as lightweight concrete blocks or lightweight mortar bricks. In the case of Pleret, Bantul, this can be done because the raw materials of pumice conglomerate could be taken from an area near the rice field regions. However, the characteristics of the lightweight concrete made of the local lightweight aggregate have not been, known yet. Therefore a research for knowing the characteristics of the concrete had to be done. In the research, pumice conglomerate cubes with 100 mm Sizes, cylinders with 300 mm length 150 mm diameter of no-fines concrete, and cubes with 70 mm sizes of lightweight mortar were tested The tests were done to find the specific gravity, water absorption, and compressive strength. The required Portland cement to make concrete and mortar were also calculated. The result indicated that the pumice conglomerate cube strength does not satisfy the requirement for making normal concrete, but it may be used for making lightweight concrete or lightweight mortar. Test results on the no fines concrete cylihders and the lightweight mortar cubes indicate that it satisfys the requirement of Indonesian Standard of Building Materials (PUBI-1982). Therefore it can be used to change the normal concrete blocks and fire bricks respectively. These materials are required small quantity of Portland cement so the cost of materials are cheap.